Incident Diabetes in Survivors of Critical Illness and Mechanisms Underlying Persistent Glucose Intolerance: A Prospective Cohort Study. Issue 2 (February 2019) - Kar, Palash; Plummer, Mark P.; Ali Abdelhamid, Yasmine; Giersch, Emma J.; Summers, Matthew J.; Weinel, Luke M.; Finnis, Mark E.; Phillips, Liza K.; Jones, Karen L.; Horowitz, Michael; Deane, Adam M.
Abstract : Objectives: Stress hyperglycemia occurs in critically ill patients and may be a risk factor for subsequent diabetes. The aims of this study were to determine incident diabetes and prevalent prediabetes in survivors of critical illness experiencing stress hyperglycemia and to explore underlying mechanisms. Design: This was a prospective, single center, cohort study. At admission to ICU, hemoglobin A1c was measured in eligible patients. Participants returned at 3 and 12 months after ICU admission and underwent hemoglobin A1c testing and an oral glucose tolerance test. Blood was also collected for hormone concentrations, whereas gastric emptying was measured via an isotope breath test. β-cell function was modeled using standard techniques. Setting: Tertiary-referral, mixed medical-surgical ICU. Patients: Consecutively admitted patients who developed stress hyperglycemia and survived to hospital discharge were eligible. Measurements and Main Results: Consent was obtained from 40 patients (mean age, 58 yr [SD, 10], hemoglobin A1c 36.8 mmol/mol [4.9 mmol/mol]) with 35 attending the 3-month and 26 the 12-month visits. At 3 months, 13 (37%) had diabetes and 15 (43%) had prediabetes. At 12 months, seven (27%) participants had diabetes, whereas 11 (42%) had prediabetes. Mean hemoglobin A1c increased from baseline during the study: +0.7 mmol/mol (–1.2 to 2.5 mmol/mol) at 3 months and +3.3 mmol/mol (0.98–5.59 mmol/mol) at 12 months ( p = 0.02). Gastric emptying was not significantly different across groups at either 3 or 12 months. Conclusions: Diabetes and prediabetes occur frequently in survivors of ICU experiencing stress hyperglycemia. Based on the occurrence rate observed in this cohort, structured screening and intervention programs appear warranted. Abstract : Supplemental Digital Content is available in the text.